Loosening Analysis for Swing Circle Tightening Body of Excavator Subjected to Impact Loading: Explicit Finite Element Approach - KAMIYA, Shota; YAMADA, Yoshikazu; IZUMI, Satoshi; SAKAI, Shinsuke (Nihon Kikai Gakkai rombunshuu. A hen, 2012)
A swing circle part of excavator involves many bolted joints subject to impact loading. Therefore, the structural integrity assessment for the loosening of the bolted joints is very important. In this paper, we have tried the loosening analysis for the bolted joints using explicit finite element method. As a check of the validity of the explicit finite element method, the loosening due to quasi-static transverse loading has been investigated by both explicit and implicit finite element methods. The result of the explicit finite element method shows good agreement with that of the implicit finite element method. The developed scheme applies to the loosening of the bolted joints in the swing circle part of the excavator subjected to impact loading. The vibration modes of the excavator model are fitted to the result of experimental modal analysis. All the bolts are modeled by rivets model and tightening force is applied. Bearing part of the swing circle is modeled by spring and dashpot elements. As a result, the acceleration of counter-weight part and the deformation shape of the bolts are successfully reproduced by our model. The stress of the bolts shows agreement within a factor of two. It is found that the safety margin for the loosening caused by bearing-surface slip is more than ten, which is sufficient in terms of engineering application.